Study of the decomposition process of local phosphorites using industrial waste sulfuric acid - Shermatov, Akramjon; Sherkuziev, Doniyor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this article, the chemical composition of products obtained by decomposing two differently composed samples of Central Kyzylkum phosphorite using industrial waste sulfuric acid was studied. During the research, the influence of reaction conditions, temperature, acid quantity, and reaction duration on the product composition was analyzed. Based on the obtained results, experiments confirmed the possibility of producing enriched superphosphate by processing simple phosphorite flour with waste acid. The study employed a Shimadzu UV 1900i spectrophotometer and titrimetric analysis methods.